ANALISIS KARAKTERRITIK PERUSAHAAN DALAM MEMPREDIKSI LUAS UNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Setyono, Rieslian Yunevida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to test and to analyze the company characteristic which consist of companyâs size, companyâs profile, profitability, leverage, and liquidity which is used in order to predict the CSR scope. The analysis technique is using Logistic Regressions because the independent variable is the mix between the continuous variable and category, while the dependent variable is a dummy variable. The companyâs size is measured by using Log n (total asset), companyâs profile is measured by classifying of the companyâs high profile and low profile, profitability is measured by using Return On Asset, Leverage is measured by using Debt To Equity Ratio, and Liquidity is measured by using current ratio. The scope of CSR disclosure is measured by using Global Reporting Initiative (GRI) in 2006. The samples are 29 manufacturer companies listed in Indonesia Stock Exchange in 2010-2012 and the number of analyzes units are 87. The samples are determined based on the purposive sampling technique by using the criteria which has been determined by the researcher. The research result shows that the profitability can be used to predict the disclosure of the CSR scope), while the companyâs size, companyâs profile, leverage, and liquidity cannot be used to predict the disclosure scope of CSR. it shows that the variables of the companyâs size, profile, leverage, and liquidity have been assumed less relevant in disclosing of the CSR scope.Keywords: companyâs size, companyâs profile, leverage, liquidity, disclosure of the CSR scope.